Long inverted repeats around the chromosome replication terminus in the model strain Bacillus thuringiensis serovar israelensis BGSC 4Q7. Issue 12 (12th December 2020) - Bolotin, Alexander; Quinquis, Benoit; Roume, Hugo; Gohar, Michel; Lereclus, Didier; Sorokin, Alexei
Abstract : Bacillus thuringiensis serovar israelensis is the most widely used natural biopesticide against mosquito larvae worldwide. Its lineage has been actively studied and a plasmid-free strain, B . thuringiensis serovar israelensis BGSC 4Q7 (4Q7), has been produced. Previous sequencing of the genome of this strain has revealed the persistent presence of a 235 kb extrachromosomal element, pBtic235, which has been shown to be an inducible prophage, although three putative chromosomal prophages have been lost. Moreover, a 492 kb region, potentially including the standard replication terminus, has also been deleted in the 4Q7 strain, indicating an absence of essential genes in this area. We reanalysed the genome coverage distribution of reads for the previously sequenced variant strain, and sequenced two independently maintained samples of the 4Q7 strain. A 553 kb area, close to the 492 kb deletion, was found to be duplicated. This duplication presumably restored the equal sizes of the replichores, and a balanced functioning of replication termination. An analysis of genome assembly graphs revealed a transient association of the host chromosome with the pBtic235 element. This association may play a functional role in the replication of the bacterial chromosome, and the termination of this process in particular. The genome-restructuring events detected may modify the genetic status of cytotoxic or haemolytic toxins, potentially influencing strain virulence. Twelve of the single-nucleotide variants identified in 4Q7 were probably due to the procedure used for strain construction or were present in the precursor of this strain. No sequence variants were found in pBtic235, but the distribution of the corresponding 4Q7 reads indicates a significant difference from counterparts in natural B. thuringiensis serovar israelensis strains, suggesting a duplication or over-replication in 4Q7. Thus, the 4Q7 strain is not a pure plasmid-less offshoot, but a highly genetically modified derivative of its natural ancestor. In addition to potentially influencing virulence, genome-restructuring events can modify the replication termination machinery. These findings have potential implications for the conclusions of virulence studies on 4Q7 as a model, but they also raise interesting fundamental questions about the functioning of the Bacillus genome.